Self-harm during the early period of the COVID-19 pandemic in England: comparative trend analysis of hospital presentations - Hawton, K; Casey, D; Bale, E; Brand, F; Ness, J; Waters, K; Kelly, S; Geulayov, G (Elsevier, 2021)
Background: The COVID-19 pandemic and public health measures necessary to address it may have major effects on mental health, including on self-harm. We have used well-established monitoring systems in two hospitals in England to investigate trends in self-harm presentations to hospitals during the early period of the pandemic.